2021
DOI: 10.1016/j.amjsurg.2020.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Better characterization of operation for ulcerative colitis through the National surgical quality improvement program: A 2-year audit of NSQIP-IBD

Abstract: Introduction: There is little consensus of quality measurements for restorative proctocolectomy with ileal pouch-anal anastomosis(RPC-IPAA) performed for ulcerative colitis(UC). The National Surgical Quality Improvement Program(NSQIP) cannot accurately classify RPC-IPAA staged approaches. We formed an IBD-surgery registry that added IBD-specific variables to NSQIP to study these staged approaches in greater detail. Methods: We queried our validated database of IBD surgeries across 11 sites in the US from March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…This study was conducted using data collected by the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP)-IBD collaborative, which was organized to improve data collection on IBD-specific outcomes via the overall ACS-NSQIP registry. 18,19 ACS-NSQIP is a nationally validated, risk-adjusted, outcomes-based program to measure and improve the quality of surgical care. We hypothesized that a risk index–based frailty assessment based on chronic diseases may not accurately predict the risk of postoperative complications in patients with IBD.…”
mentioning
confidence: 99%
“…This study was conducted using data collected by the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP)-IBD collaborative, which was organized to improve data collection on IBD-specific outcomes via the overall ACS-NSQIP registry. 18,19 ACS-NSQIP is a nationally validated, risk-adjusted, outcomes-based program to measure and improve the quality of surgical care. We hypothesized that a risk index–based frailty assessment based on chronic diseases may not accurately predict the risk of postoperative complications in patients with IBD.…”
mentioning
confidence: 99%
“…At high-volume centers, the majority of surgery in the elective setting is currently being performed using a minimally invasive approach [44]. There are many who advocate for laparoscopic or robotic approaches to these procedures, and much has been written on the advantages of a minimally invasive approach including less intraoperative blood loss, decreased LOS, faster return of bowel function, and improved 30-day outcomes [45][46][47].…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the majority of IPAAs are currently created with a protective loop ileostomy. A recent analysis of high-volume IBD centers in the US showed that only 5.5% of IPAAs were undiverted [44].…”
Section: Surgical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 A similar NSQIP initiative is underway for operations performed for inflammatory bowel disease. 19 20…”
Section: Common National Databases For the Colorectal Surgeonmentioning
confidence: 99%